Merdeka Award gives us the heroes we need - Abd Razak, Dzulkifli (2009)
MALAYSIANS must surely be proud that when the nation commemorated its 50 years of independence two years ago, the occasion also marked the establishment of the Merdeka Award to celebrate the true spirit of independence and the pursuit of excellence. This is particularly significant because there is now a platform to recognise individuals for their "outstanding and lasting contributions to the nation and the people of Malaysia". In other words, Malaysia can add to its list of national heroes, people who have made arduous attempts to ensure that the nation's independence is more meaningful and robust.